Implementation of Advanced Coal-Biomass Blending and Fuel Stock Management at Pelabuhan Ratu Power Plant - Nurahman, Herowiko Thama; Hermawan, Heru (Journal of Mechanical Design and Testing, 2024)
The issue of climate change is of particular concern to countries around the world, including Indonesia. Many efforts are being and will be made to contribute to addressing climate change issues. Pelabuhan Ratu Power Plant (3 x 350 MW) belongs to PT PLN Indonesia Power. In line with the PLN Transformation (GREEN aspect) and the PT PLN Indonesia Power program ("Green Boosters"), Pelabuhan Ratu Power Plant contributes to produce low-carbon sustainable energy by cofiring biomass (sawdust). There are two main challenges in implementing cofiring. The first is the poor biomass handling and blending methods that are typically used in power plants. The second is the low calorific value of coal and biomass blending due to the improper blending process. To overcome these challenges, Pelabuhan Ratu Power Plant has developed an advanced coal-biomass blending and fuel stock management digitalization. By applying advanced method of coal-biomass blend, the biomass utilization (total, monthly average, and daily average) increased significantly in 2022 and 2023. Total biomass utilization increased up to 171% and still possible to be higher. The green energy production increased up to 255% and GHG emission reduced up to 255%. The fuel stock management provides optimal blending recommendations as operators' guidelines. As a result, potential derating loss due to low calorific value of blended products can be reduced by 59.9%.